Ethics in Research Principles and Practical Considerations - Congiunti, Lorella; Lo Piccolo, Francesco; Russo, Antonio; Serio, Mario (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book draws a connection between ethics and research across social sciences, philosophy, medical sciences and legal sciences, and demonstrates that any research activity needs to be conducted by means of rules deriving from the field of ethics. Although having a common core, such rules assume different characteristics depending on the branch of science, as the contributions on philosophy, medicine, dentistry, law, biotechnology, robotics and architecture highlight. It also investigates the more complex ethical concerns and places them in a larger, technological context. Starting with an introduction to common-sense ethical principles, the contributions then guide the reader, helping them develop and understand a comprehensive knowledge on the field. Notably, it appeared interesting to analyze recent events related to the arrival of the Sars-CoV-2 pandemic in light of ethical principles, highlighting in what terms their applicability can still be confirmed. Moreover, the book makes these topics accessible to a non-expert audience, while also offering alternative reading pathways to inspire more specialized readers.
"Philosophy and medicine. The search for happiness" -- "Ethics in legal research" -- "Ethics in life sciences and research" -- "Therapeutic strategies and self-determination: Lessons from Covid-19 pandemic" -- "Ethics and integrity in academic publishing" -- "Ethics in architecture and in the humanistics research" -- "Towards virtuous machines: When ethics meets robotics" -- "How the love of truth challenges the researcher's function: References in the scientific field of business administration" -- "The humanization of health care: In-depth knowledge regarding the ethics of dental care in oncological patients".
Keywords: Bioethics; Technology -- Moral and ethical aspects; Medical Ethics; Bioethics; Ethics of Technology; Medical Ethics